ANALISIS MOTIVASI BELAJAR MELALUI MEDIA PAPAN TEMPEL PADA MATERI BAHAN DASAR PAKAIAN DI KELAS IIIB - Norra Mutiara.K; Rina Dwi.S; Fenny Roshayanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims is to describe the learning motivation of students in learning the basic material of clothing. Types of descriptive research. The subject for this research was 23 students of class IIIB at Bendungan Elementary School consisting of 13 girls and 10 boys. Data collection methods used are questionnaires, observation, and documentation. Motivational data were obtained using questionnaires and documentation. Meanwhile, to support the research data, it was carried out by observing the state of the class. Data analysis was performed using descriptive qualitative. The questionnaire used is closed, in this questionnaire, respondents can only answer with the choices provided by the researcher. The research results obtained the researcher obtained a final score of 48 questions and 23 respondents, namely 3104, and obtained an average of 65% which was classified as quite good. Meanwhile, 9 children got very good criteria, and 14 students got good criteria. Statements of research data with a total of 48 statements, classified into 4 groups, namely always, often, sometimes, and never.